CONTRASTIVE ANALYSIS OF TENSE AND ASPECT IN ENGLISH AND INDONESIAN LANGUAGE - Bejo Sutrisno; Ana Ratna Sari (Journal of English Language and Literature (JELL), 2018)
This study aims to find out the comparison between English and Indonesian terms of finite verb form, tense and aspect. Language is the medium used by human to convey the contents of their minds. Language is also an object of study in educational institutions. Examples of interesting language to study and learn are English and Indonesian language, because each of them has distinct characteristics. The method used in this research is descriptive qualitative study. The result of this study shows that there are four groups of verb forms in English: simple, continuous, perfect and perfect continuous forms. Each of the groups has present, past, and future forms. This scientific paper will contribute empirical data from English and Indonesian language that will support contrastive analysis theory.